Durability evaluation of geopolymer and conventional concretes. (1st April 2017) - Albitar, M.; Mohamed Ali, M.S.; Visintin, P.; Drechsler, M.
Highlights: Geopolymer concretes are superior to conventional concrete in an acidic environment. Fly ash and GLSS concretes are more chemically stable than conventional concrete. OPC concrete has lower water absorption and sorptivity than geopolymer concretes. Geopolymer concretes exhibit superior mechanical properties under chemicals attack. Abstract: Durability of concrete strongly influences the service life of structural members. Durable concrete protects embedded reinforcing steel from corrosion and reduces the potential for concrete spalling under chemical attack. This paper evaluates the performance of geopolymer concretes manufactured using either class-F fly ash or blended fly ash and granulated lead smelter slag (GLSS). The performance of ordinary Portland cement (OPC) concrete is also investigated as a reference for evaluating the durability characteristics of geopolymer concretes. All concrete specimens were continuously immersed up to nine months in four different chemical solutions: 5% sodium chloride, 5% sodium sulphate, 5% sodium sulphate + 5% magnesium sulphate, and 3% sulphuric acid. Throughout the exposure period, the change in mass, compressive strength, splitting tensile strength, flexural strength, water absorption, sorptivity and porosity were evaluated. The influence of wetting–drying and heating–cooling cycles on the mass loss and compressive strength was also investigated. The results revealed that the OPC concrete has lower water absorption and sorptivity than the geopolymer concrete. Furthermore, it is shown that sodium sulphate has the greatest impact on geopolymer concretes, while OPC concrete is more susceptible to sulphuric acid attack. The results showed that, in general, the durability performance of geopolymer concrete is superior to that of OPC concrete within the range of the considered exposure.